Effectivity of bulrush (Scirpus californicus.) as a soil conditioner in increasing sandy and clay soil fertility - Munifatul Izzati; SRI HARYANTI; RINI BUDI HASTUTI (Society for Indonesian Biodiversity, 2021)
Abstract. Izzati M, Haryanti S, Hastuti RB. 2021. Effectivity of bulrush (Scirpus californicus) as a soil conditioner increasing sandy and clay soil fertility. Biodiversitas 22: 3423-3429. Bullrush (Scirpus californicus) is a species of macrophytes that often populates lakesides. This aquatic plant was rarely studied and its use has not been explored yet. This study was carried out to determine the effects of soil conditioner made from bulrush on sandy and clay soil fertility. Collected bulrush from Rawa Pening lake was milled into a powder and used as a soil conditioner in a proportion of 1:1. After a week, soil fertility was evaluated including organic matter content, water retention, the ratio of C/N, and bacteria population. The study was designed using a Completely Randomized Design with two treatments and control. Resulted data were analyzed using a t-test to evaluate the difference between the two treatments. Results showed that bulrush powder application significantly increased sandy and clay soil fertility. The organic matter content significantly increased in both sandy (p<0,01) and clay soils (p<005). The water retention of sandy soil was increased by 74% (p<0,01), while in clay soil was reduced by 27% (p<0,01). The C/N ratio was significantly reduced in both sandy and clay soil (p<0,05), while the bacteria population significantly increased (p<0,01). It is suggested to use the bulrush as a soil conditioner particularly for sandy and clay soils.